Brevibacillin 2V, a Novel Antimicrobial Lipopeptide With an Exceptionally Low Hemolytic Activity - Zhao, Xinghong; Wang, Xiaoqi; Shukla, Rhythm; Kumar, Raj; Weingarth, Markus; Breukink, Eefjan; Kuipers, Oscar P. (Frontiers in Microbiology, 2021)
Bacterial non-ribosomally produced peptides (NRPs) form a rich source of antibiotics, including more than twenty of these antibiotics that are used in the clinic, such as penicillin G, colistin, vancomycin, and chloramphenicol. Here we report the identification, purification, and characterization of a novel NRP, i.e., brevibacillin 2V, from Brevibacillus laterosporus DSM 25. Brevibacillin 2V has strong antimicrobial activity against Gram-positive bacterial pathogens, including difficult-to-treat antibiotic-resistant Enterococcus faecium, Enterococcus faecalis, and Staphylococcus aureus. Notably, brevibacillin 2V has a much lower hemolytic activity and cytotoxicity to eukaryotic cells than previously reported NRPs of the lipo-tridecapeptide family, including other brevibacillins, which makes it a promising candidate for antibiotic development. In addition, our results demonstrate that brevibacillins display synergistic action with established antibiotics against Gram-negative bacterial pathogens. Probably due to the presence of non-canonical amino acids and D-amino acids, brevibacillin 2V showed good stability in human plasma. Thus, we identified and characterized a novel and promising antimicrobial candidate (brevibacillin 2V) with low hemolytic activity and cytotoxicity, which can be used either on its own or as a template for further total synthesis and modification.